2018
DOI: 10.12659/ajcr.911106
|View full text |Cite
|
Sign up to set email alerts
|

Giant Splenic Aneurysm with Arteriovenous (A-V) Shunt, Portal Hypertension, and Ascites

Abstract: Patient: Male, 43Final Diagnosis: Splenic aneurysmSymptoms: Ascites • fever • portal hypertensionMedication: —Clinical Procedure: —Specialty: SurgeryObjective:Rare co-existance of disease or pathologyBackground:Splenic aneurysms are rare, asymptomatic, and usually derive from previous surgical interventions. Endovascular repair is the best option, but when A-V shunt is present, open repair might be more suitable.Case Report:A 43-year-old man presented to the Internal Medicine Department of AHEPA University Hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Chadha et al [ 35 ] reported the case of a 66-year-old male with an acquired SV aneurysm and described novel use of a “ Sundt external carotid endarterectomy shunt ” as a temporary portacaval shunt to control portomesenteric hypertension, before transplantation of the liver. A giant SV aneurysm 98 mm in size developed as a consequence of a splenectomy, an arteriovenous fistula and portal hypertension; this aneurysm was treated successfully with open surgery[ 36 ].…”
Section: Etiology Multimodal Imaging and Current Managementmentioning
confidence: 99%
“…Chadha et al [ 35 ] reported the case of a 66-year-old male with an acquired SV aneurysm and described novel use of a “ Sundt external carotid endarterectomy shunt ” as a temporary portacaval shunt to control portomesenteric hypertension, before transplantation of the liver. A giant SV aneurysm 98 mm in size developed as a consequence of a splenectomy, an arteriovenous fistula and portal hypertension; this aneurysm was treated successfully with open surgery[ 36 ].…”
Section: Etiology Multimodal Imaging and Current Managementmentioning
confidence: 99%